HUBUNGAN FLAT FOOT DENGAN KESEIMBANGAN STATIS DAN DINAMIS PADA ANAK SEKOLAH DASAR NEGERI 4 TONJA KOTA DENPASAR - Kadek Ady Antara; I Nyoman Adiputra; I Wayan Sugiritama (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACTThe development of balance during child growth is very important to be reviewed. Deformity of the sole of the foot isone of the causes of disturbance of balance. This research is analytic with cross sectional approach. In 101 samples(58 male samples, 43 female samples), age 6-11 years, the measured independent variable was flat foot through thewet footprint test. The dependent variables measured were static balance through standing stork test, and dynamicbalance through Balance beam test. In Spearman's rho data analysis calculation known value of significance (2-tailed) is 0,000 for static and dynamic balance, which means significance value <?. Furthermore, it is known CorrelationCoefficient (correlation coefficient) of 0.933 for static balance, and 0.828 for dynamic equilibrium. Based on thedata output, it can be concluded that there is a strong, significant, and unidirectional relationship between the flat footwith static and dynamic balance in the 4th school elementary school of the 4th city of Denpasar.Keywords: Flat Foot, Static Balance, Dynamic Balance